Thermodynamic properties of titanium-manganite LaСаTiMnO6 - Kasenov, B.K.; Kasenova, Sh.B.; Sagintaeva, Zh.I.; Baisanov, C.O.; Lu, N.Yu.; Bekturganov, Zh.S.; Zeinidenov, A.K.; Kuanyshbekov, E.E. (Bulletin of the Karaganda University. “Physics” Series., 2023)
By the method of dynamic calorimetry in the range of 298.15-673 K, the heat capacity of titanium-manganite LaСаTiMnO6, obtained by solid-phase interaction at 800-1200oC from lanthanum, titanium (II), manganese (III) and calcium carbonate oxides was studied. On the dependence curve Ср~(T) in the specified temperature range, a λ-shaped effect was detected at 598 K, probably related to the phase transition of the second kind. A fundamental constant is determined — the standard heat capacity of LaСаTiMnO6, equal to 22114 J /(molK). Its standard entropy, equal to 2066 J/(molK), was estimated by the approximate method of ion increments. Based on experimental data, taking into account the temperature of the phase transition, the equations describing the temperature dependences of Ср~(T) and the thermodynamic functions So(T), Ho(T) — Ho(298.15) and Фхх(Т) of the investigated titanium-manganite lanthanum and calcium are calculated. The standard heat capacity of LaСаTiMnO6 is also calculated using the Debye method, the value of which is in good agreement with experimental data. According to the developed methodology, the standard enthalpy of titanium-manganite formation was calculated, equal to — 3867.5 kJ/mol.
Keywords: Titanium-manganite; lanthanum; calcium; heat capacity; phase transition; enthalpy of formation; thermodynamic properties